A Tragedy of Memory - Lombardo, Agostino (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2018)
Agostino Lombardo investigates the manifold uses of memory in Antony and Cleopatra which range from the historical and literary tradition, which lie behind the play, with which an Elizabethan audience would have been familiar, to the specific theatrical recollection of the performance of Shakespeare’s own Julius Caesar. The inclusion of memory as well as enriching the experience of the play itself expands the possibility for the theatre to be an image of life which, like the theatre, takes place in the present but is nurtured by the past. Keywords: Antony and Cleopatra, Julius Caesar, Memory, Theatre, Collective imagination